Diaspora Networks as a Financial Catalyst: Navigating Global Markets for Kediri’s SMEs in the Netherlands and Australia - Pramana, Andy Chandra; Sudarmiatin; Pratikto, Heri (Universitas Kadiri, 2026)
This study analyzes how diaspora networks serve as financial catalysts for 47 Micro, Small, and Medium Enterprises (MSMEs) in Kediri, focusing on the culinary and creative industry sectors. The research explores combining domestic resources with global diaspora networks to mitigate financial constraints during internationalization. A qualitative approach with a multi-case study design was employed. Data was triangulated using semi-structured interviews, digital and field observations, and document studies , and was subsequently analyzed via Cross-Case Synthesis. The findings reveal that diaspora networks in the Netherlands and Australia act as crucial